Fractographic Analysis of Tensile Failures of Zirconia Epoxy Nanocomposites (Baghdad Science Journal, 2022)
This work characterizes the fractographic features of the neat epoxy and ZrO2 epoxy nanocomposites. All samples were subjected to a tensile test to determine the tensile strength and tensile modulus. SEM images were used to study the morphology of the fractured surface. The fractographic of the fracture surfaces were studied by microstructure analysis program (j-images) to specify the effect of ZrO2 nanoparticles on tensile performance and failure mechanism for ZrO2 epoxy nanocomposites. The tensile test results show that the addition of ZrO2 nanoparticles (2, 4, 6, 8, and 10 vol.%) to the epoxy matrix leads to increase the tensile strength about 40% for optimal content of ZrO2 nanoparticles at 4 vol.%, tensile modules of ZrO2 epoxy nanocomposites increased about 200% for optimal content of ZrO2 nanoparticles at 4 vol.%. SEM images show that the patterns of fractured surfaces of ZrO2 epoxy nanocomposites are different from the pattern of the neat epoxy. The fracture roughness of ZrO2 epoxy nanocomposites increased with the increases of the percentages of ZrO2 nanoparticles, where the increment of fracture roughness about 30% for optimal content of ZrO2 nanoparticles at 4 vol.% can be indicator for the improvement of mechanical properties (tensile strength and modules).